Systematic Review: Adverse Effects Associated with Faecal Matter Transplant - Gonçalo de Almeida Pinto Soares (2021)
Background: The concept of faecal matter transplant has evolved over time. The first and better-known application is in the context of diarrhea caused by recurrent or refractory infection with Clostridium difficile. Presently there are numerous pathologies where the application has proven potential to be beneficial. Nevertheless, this therapeutic strategy lacks studies that address the adverse effects that may result from it. This systematic review aims to evaluate the concerns of safety during the procedure. Methods: A total of 5965 studies, obtained in 3 different databases, regarding FMT were identified but only 97 met the eligibility criteria. In these studies, 3563 patients submitted to the FMT procedure in the context of several pathologies were identified. Results: The total incidence rate of AEs related to FMT procedure was 20,3% (725/3564). 28 different types AEs were described with the most common being diarrhea, abdominal pain and flatulence. It should be noted that when comparing articles related to CDI and non-CDI, the incidences are 16.8% and 32.4% respectively. Analysing by route of administration, the overall incidence of AEs drops from 37.9% for the upper GIT routes of FMT to 14,0% for lower GIT routes. A total of 12 new diagnoses were described in 9 different articles. Death associated to the FMT procedure happened on 3 patients with a mortality rate of 0.08% (3/3563). Conclusion: This systematic review demonstrated that there are risks in the FMT procedure, but when the technique is adequate and the risk benefit ratio well balanced it is an interesting therapeutic strategy to consider within the appropriate regulatory context.